How prosperous were the Romans? Evidence from Diocletian's price edict (301 AD) - Allen, R (2007)
The paper compares the standard of living of labourers in the Roman Empire in 301 AD with the standard of living of labourers in Europe and Asia from the middle ages to the industrial revolution. Roman data are drawn from Diocletian’s Price Edict. The real wage of Roman workers was like that of their counterparts in the lagging parts of Europe and much of Asia in the middle of the eighteenth century. Roman workers earned just enough to buy a minimal subsistence consumption basket. Real wages were considerably higher in the advanced parts of Europe in the eighteenth century, as they had been in Europe generally following the Black Death in 1348-9.